Best Answer

To simplify expression 5x + 9 - 7x - 11, you can combine the x terms (5x - 7x) to get -2x, and combine the constant terms (9 - 11) to get -2. Therefore, the simplified expression is -2x - 2.

More answers

If you mean: 5x+9+7x-11 then it simplifies to 12x-2

Q: How do you Simplify 5x 9 7x-11?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

7 & 11 have no common factor: both are prime.

minus 4 plus 9 = 5, so 5x

Set up the equation and solve: -27 = 8x - 5x (next simplify by subtracting 5x from 8x)) -27 = 3x (next divide both sides of the equation by 3) -27/3 = 3x/3 (next simplify and solve) -9 = x

5x +50x

5x^2 + 14x - 3x^2 - 9 = 2x^2 + 14x - 9

Related questions

9(5x) = 45x simplified

6x - 9 - x = 6Combine like terms on the left side:5x - 9 = 6Add 9 to each side:5x = 15Divide each side by 5:x = 3By the time you simplify it, you've solved it.

7 & 11 have no common factor: both are prime.

5x - 4x = x

minus 4 plus 9 = 5, so 5x

Set up the equation and solve: -27 = 8x - 5x (next simplify by subtracting 5x from 8x)) -27 = 3x (next divide both sides of the equation by 3) -27/3 = 3x/3 (next simplify and solve) -9 = x

5x +50x

5x^2 + 14x - 3x^2 - 9 = 2x^2 + 14x - 9

you can't because it is not an equation but you can simplify it. The simplified version would be 5x times 9

2x plus 5x simplified is 7x.

7x11 is 77

3x = 5x - 10 Subtract both sides by 5x 3x - 5x = 5x - 10 - 5x Simplify - 2x = - 10 Divided both sides by -2 to isolate x - 2x / - 2 = - 10 / - 2 Simplify x = 5 Plug x into the original equation. 3(5) = 5(5) - 10 = ? Simplify 15 = 25 - 10 = ? Simplify 15 = 15 = ? Therefore 3x = 5x - 10 = 15